Pengaruh Model Pembelajaran Discovery Learning Terhadap Pemahaman Konsep dan Hasil Belajar Siswa pada Materi Teorema Pythagoras - Besin, Yanuaria Fore; Ema, Helena Lolyta; Kaluge, Agapitus Hendrikus (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of the Discovery Learning model on students' conceptual understanding and learning outcomes in the Pythagorean Theorem material. The study used a quantitative approach with a quasi-experimental design of the One Group Pretest–Posttest Design, involving 32 eighth-grade students at SMP Negeri 1 Kupang. The research instruments were conceptual understanding tests and student learning outcome tests. The data were analyzed using the Shapiro–Wilk normality test and the paired sample t-test through SPSS to determine the difference in scores before and after the implementation of learning. The results showed that the pre-test and post-test data were normally distributed, thus fulfilling the assumptions of parametric testing. The average pre-test score of 71.13 increased to 83.19 on the post-test, with a difference of 12.06 points. The paired sample t-test resulted in a t-value of -11.108 with a significance level of p = 0.000 (< 0.05), indicating a significant difference between the pre-test and post-test scores. These findings indicate that the Discovery Learning model has a significant effect on improving students' conceptual understanding and learning outcomes in the Pythagorean Theorem material. Thus, Discovery Learning can be used as an effective and relevant alternative learning model in mathematics education.